Regional Analysis of Consecutive Days Maximum Rainfall Using L-Moments: A Case Study for Brahmaputra Valley Region of Assam, India - Bora, Rubul; Bhuyan, Abhijit; Kumar Dutta, Biju (Communications in Mathematics and Applications, 2022)
In this study, Regional Rainfall Frequency analysis has been carried out based on L-moment in the Brahmaputra Valley. For this purpose, the consecutive 1 to 6 days maximum rainfall for 11 sites (data varying from 14 years to 23 years) have been considered for our study. The heterogeneity measures for 1 to 6 days of the study region are calculated. The five probability distributions namely, generalized extreme value (GEV), generalized logistic (GLO), generalized Pareto (GPA), generalized normal (GNO), and the Pearson Type III (PE3) have been considered. The Z-statistics criteria and L-moment ratio diagram for goodness of fit tests have been used for identifying the best fitting distributions for 1 to 6 days of the study area. The PE3 distribution is identified as the best fitting distribution for the consecutive 1-day and 6-days maximum rainfall while GLO distribution for the consecutive 2-days and 4-days, GNO distributions for the consecutive 3-days and 5-days maximum rainfall of the study region. The regional relationships for each season of the study regions are develope
Keywords: Probability; Distribution; L-moment; Heterogeneity; Z-statistics; L-moment ratio diagram